(untitled) (Research, Society and Development, 2023)
Introduction: Congenital generalized lipodystrophy is a pathology that presents a wide range of clinical manifestations, with numerous risk factors and a high rate of complications. Objective: The objective of this work is to review the literature on congenital lipodystrophy, presenting the clinical picture, diagnosis and recommended treatment, taking into account the low incidence of reported cases and the severity of the pathology. Method: A narrative literature review was performed using the databases: PubMed, Scielo and UpToDate. The descriptors used were: “Lipodystrophy”; “Congenital Generalized Lipodystrophy”, “Insulin Resistance” and “Metabolic Syndrome”. Complete articles were selected, found in the following languages: Portuguese, English or Spanish. 298 articles were pre-selected and after verifying the inclusion and exclusion criteria, 33 studies remained that were used to compose the work. Results and discussion: Pathophysiology is associated with mutations in genes that code for different proteins, which are involved in the various stages of lipid droplet formation in adipocytes. The most reported clinical picture is related to hepatomegaly and muscle hypertrophy, but the characteristics can be variable because it is an important genetic alteration. There is a frequent association with glucose intolerance, hyperinsulinism, diabetes mellitus, hypertriglyceridemia, hepatic steatosis, prominent musculature, hypertrophic cardiomyopathy and cysts. The diagnosis is usually clinical, but needs confirmation through genetic testing. Treatment is related to the severity and complications presented by the individual. Conclusion: studies on the subject are necessary to guarantee early diagnosis and follow-up of individuals from the pediatric stage.